Pemberdayaan Wanita Nelayan melalui Souvenir Kerajinan Cangkang Kerang dalam Meningkatkan Perekonomian di Desa Pohuwato Kecamatan Marisa: Empowering Fishermen Women through Shell Craft Souvenirs in Improving the Economy in Pohuwato Village, Marisa District - Lanto Miriatin Amali; Fitri Hadi Yulia Akib (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
As integral pillars of the fisherman's family and a significant contributor to the family economy, this service program aims to empower fisherwomen to improve the economy through handicrafts offered as souvenirs. An effort to empower women by employing human resources entails the production of handicrafts as souvenirs, which has implications for improving the standard of living for fishing households. Twenty fisherwomen from each Dusun (sub-village) in Pohuwato Timur village participate in the service program. A Pohuwato Timur village office held this community service project for a week, from October 23 to October 29, 2022. The results of this community service demonstrate that the understanding of the subject material and the benefits of the purpose of this service reach a scale of 4, or that understanding of the waste from clam shells is incredibly helpful and valued more. In contrast, the demonstration results indicate a scale of 5, or very good, in the lessons for making handicrafts as souvenirs from shell waste. Moreover, it is expected that the results of this service would change the mindset of fisherwomen, allowing women to achieve more of their potential while also being one of the outstanding products of the village and a product with a high value.